Mapping the intellectual structure and landscape of nano-drug delivery systems in colorectal cancer - Chang, Yonglong; Ou, Qinling; Zhou, Xuhui; Nie, Kechao; Yan, Haixia; Liu, Jinhui; Li, Jing; Zhang, Sifang (Frontiers in Pharmacology, 2023)
Background: Colorectal cancer (CRC) is a prevalent malignancy affecting the digestive tract, and its incidence has been steadily rising over the years. Surgery remains the primary treatment modality for advanced colorectal cancer, complemented by chemotherapy. The development of drug resistance to chemotherapy is a significant contributor to treatment failure in colorectal cancer. Nanodrug delivery systems (NDDS) can significantly improve the delivery and efficacy of antitumor drugs in multiple ways. However, there is a lack of visualization of NDDS research structures and research hotspots in the field of colorectal cancer, and the elaboration of potential research areas remains to be discovered. Objective: To comprehensively explore the current research status and development trend of NDDS in CRC research. Methods: Bibliometric analysis of articles and reviews on NDDS for CRC published between 2002 and 2022 using tools including CiteSpace, VOSviewer, R-bibliometrix, and Microsoft Excel was performed. Results: A total of 1866 publications authored by 9870 individuals affiliated with 6126 institutions across 293 countries/regions were included in the analysis. These publications appeared in 456 journals. Abnous Khalil has the highest number of publications in this field. The most published journals are the International Journal of Nanomedicine, International Journal of Pharmaceutics, and Biomaterials. Notably, the Journal of Controlled Release has the highest citation count and the third-highest H-index. Thematic analysis identified "inflammatory bowel disease," "oral drug delivery," and "ulcerative colitis" as areas requiring further development. Keyword analysis revealed that "ulcerative colitis," "exosomes," and "as1411" have emerged as keywords within the last two years. These emerging keywords may become the focal points of future research. Conclusion: Our findings reveal the current research landscape and intellectual structure of NDDS in CRC research which helps researchers understand the research trends and hot spots in this field.